Adhesion of rheumatoid peripheral blood and synovial fluid mononuclear cells to high endothelial venules of gut mucosa. - Kadioglu, A (1992)
Mononuclear cells isolated from paired blood and synovial fluid of seven patients with rheumatoid arthritis showed cytoadherence to porcine Peyer's patch high endothelial venules using the Stamper-Woodruff method. A significantly greater proportion of binding was found among the synovial fluid lymphocytes. These would appear to be a population of cells that share adherence characteristics with cells known to be of gut mucosal origin, suggesting that in rheumatoid arthritis some lymphocytes derived from mucosa migrate to joints.